Diatom boron isotope data from ODP Site 882 over the intensification of Northern Hemisphere Glaciation - Hannah Donald; George E A Swann; James W B Rae; Gavin L Foster (PANGAEA, 2024)
Diatom boron and boron isotope data from ODP Site 882 in the subarctic Pacific Ocean over the intensification of Northern Hemisphere glaciation (iNHG) at 2.73 Ma.